2020
DOI: 10.1111/cla.12445
|View full text |Cite
|
Sign up to set email alerts
|

Two centuries of distribution data: detection of areas of endemism for the Brazilian angiosperms

Abstract: Brazil has high levels of biodiversity and has received strong criticism for the increasing country-wide deforestation that threatens it. Although a significant percentage of land area in Brazil is protected, the areas are insufficient and unevenly distributed. Many studies have contributed to the biogeographical knowledge of Brazilian flora, but no endemicity analysis (EA) has been conducted including all endemic angiosperms. We investigated the spatial component, drawing on a huge and taxonomically diverse d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 101 publications
0
18
0
4
Order By: Relevance
“…4). Indeed, these provinces are extremely relevant in terms of biodiversity, with high species diversity and levels of endemism representing areas of endemism in Brazil (Gomes‐da‐Silva and Forzza, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Indeed, these provinces are extremely relevant in terms of biodiversity, with high species diversity and levels of endemism representing areas of endemism in Brazil (Gomes‐da‐Silva and Forzza, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The Brazilian flora comprises approximately 46 975 native species of plants, algae, and fungi, with 32 696 species of angiosperms, 1380 species of ferns, 1584 species of bryophytes, and 23 species of gymnosperms (The Brazil Flora Group (BFG), 2021). According to Gomes‐da‐Silva and Forzza (2020), Brazil has 132 areas of endemism, 18 for basal angiosperms, 44 for monocots, and 70 for eudicots, representing 173 families of flowering plants distributed in the country. Species diversity in Brazil is strongly associated with tropical rainforests, although an important part of the Brazilian biodiversity is restricted to the top of mountain ranges (Bitencourt and Rapini, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, knowledge of diversity in Brazil is highly uneven, the Atlantic Rainforest and the Cerrado being much more densely sampled than the Amazon, Caatinga, Pantanal, and Pampa (Antonelli & al., 2018; Stropp & al., 2020). For instance, recent studies have shown that about 50% of the Amazon is undersampled (see Costa & al., 2020; Stropp & al., 2020; Gomes‐da‐Silva & Forzza, 2021). The Amazon flora is also underrepresented in herbaria (Paton & al., 2020), highlighting the great need for improved collection efforts in this phytogeographic domain.…”
Section: Brazilian Flora 2020: An Updated Account Of Algae Fungi and ...mentioning
confidence: 99%
“…To address this issue, we should focus collection efforts on taxa with low sampling efforts or in undersampled areas (Antonelli & al., 2018; Paton & al., 2020; Stropp & al., 2020). For example, Amazonia remains the most undersampled region in the country (see Costa & al., 2020; Ritter & al., 2020; Stropp & al., 2020; Gomes‐da‐Silva & Forzza, 2021). Also undersampled are Brazil's mesophotic ecosystems (deep‐water habitats), which are home to the most extensive beds of rhodoliths in the world.…”
Section: Gaps and Future Goals Beyond 2020mentioning
confidence: 99%
“…The Brazilian Cerrado is a global biodiversity hotspot, hosting thousands of endemic and endangered species (Strassburg et al 2017;Gomes-da-Silva & Forzza 2020;Myers et al 2000). According to the Brazilian Flora 2020 project (Flora do Brasil 2020), at least 12 433 angiosperm species occur in the Cerrado domain, of which 5036 are restricted to the area.…”
Section: Introductionmentioning
confidence: 99%